Pengaruh Motivasi dan Lingkungan Kerja terhadap Kinerja Pegawai Politeknik Keuangan Negara STAN - Aulianadewi, Tandika; Siska, Elmira (Jurnal Bintang Manajemen, 2024)
The STAN State Financial Polytechnic is an official university institution within the Ministry of Finance of the Republic of Indonesia that is responsible to the Minister of Finance through the Financial Education and Training Agency (BPPK) of the Ministry of Finance of the Republic of Indonesia. This study aims to determine the influence of Motivation and Work Environment on the Performance of STAN State Financial Polytechnic Employees. The employee population in this study is 261 employees. The sample used in this study was 78 employees who used the purposive sampling technique with criteria, namely Non-State Employees (PPNPN) who had a working period of more than 1 year. Data collection techniques through google form questionnaires. The research methods that will be used are validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, linearity tests, multiple linear regression tests, t tests and F tests and determination coefficient tests. The results of this study show that partially motivation has a positive and significant effect on employee performance. Partially, the work environment has a positive and significant effect on employee performance. And simultaneously motivation and work environment have a positive and significant effect on employee performance.